The Effect of Board of Gender Diversity and Institutional Ownership on Tax Aggressivity with Audit Quality as A Moderation Variable - Eris Nanda Mufarikha; Rosidi Rosidi; Wuryan Andayani (PT. EQUATOR SINAR AKADEMIA, 2023)
The aims of this research are 1) to find out whether there is a negative effect between board gender diversity on tax aggression; 2) to find out whether there is a positive effect between institutional ownership on tax aggression; 3) to find out whether there is board gender diversity effect on tax aggression with audit quality as a moderating variable; and 4) to determine whether there is an effect of institutional ownership on tax aggression with audit quality as a moderating variable. The research approach used in this study is quantitative. The sample in this study was 17 mining companies. The method in this study is Moderated Regression Analysis (MRA). The results of this study show that board gender diversity and institutional ownership harm tax aggressiveness. Moderation variable test results, audit quality is not able to moderate the relationship between board gender diversity on tax aggressiveness and institutional ownership on tax aggressiveness.